2015
DOI: 10.1177/0194599814567111
|View full text |Cite
|
Sign up to set email alerts
|

228 Cases of Cochlear Implant Receiver‐Stimulator Placement in a Tight Subperiosteal Pocket without Fixation

Abstract: The tight subperiosteal pocket without fixation is a safe, durable, and time-saving technique for RS placement during cochlear implantation. Notably, device migration and flap complications are very uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 21 publications
1
25
1
Order By: Relevance
“…RS anchorage is performed to avoid any RS migration that might result in electrode displacement, implant extrusion and wire fatigue, resulting in device failure . Several methods of RS anchorage for the adult population have been proposed, including bony well drilling, tight subperiosteal pocket alignment, miniplate adaptation and sutures . Well drilling has been abandoned by some surgeons in favor of other alternative RS fixation techniques in an effort to reduce operative time.…”
Section: Discussionmentioning
confidence: 99%
“…RS anchorage is performed to avoid any RS migration that might result in electrode displacement, implant extrusion and wire fatigue, resulting in device failure . Several methods of RS anchorage for the adult population have been proposed, including bony well drilling, tight subperiosteal pocket alignment, miniplate adaptation and sutures . Well drilling has been abandoned by some surgeons in favor of other alternative RS fixation techniques in an effort to reduce operative time.…”
Section: Discussionmentioning
confidence: 99%
“…As the duration of surgery decreases, so does the exposure to anaesthesia and the cost of surgery. It was reported that surgery duration was significantly lower (up to 30 per cent) for the subperiosteal pocket technique in previous studies 12 , 15 . Although surgery duration was not analysed in the present study, it is known that drilling a bone implant bed and suture fixation prolongs surgery, but experienced surgeons can complete cochlear implant surgery in 30–40 minutes.…”
Section: Discussionmentioning
confidence: 56%
“…In our study, there was no intraoperative or intracranial complications observed in either groups, besides the device migration [4] [5].…”
Section: Discussionmentioning
confidence: 91%
“…In some cases, exposure of the dura is required and complications such as epidural hematoma, subdural hematoma, temporal lobe infarction and dural tears with cerebrospinal fluid leak can arise, although rare [4]- [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation